AI-Enhanced Health Counseling: A Futuristic Approach to Holistic Well-Being - Romero, Cyril B.; Subardjo, Ratna Yunita Setiyani (The Indonesian Institute of Science and Technology Research, 2024)
Artificial Intelligence (AI) in healthcare has drawn a lot of interest, especially in health counseling. Research on embodied AI has demonstrated emerging clinical significance for therapeutic applications in mental health services. AI in health counseling has a bright future, certain issues still need to be resolved. It is important to carefully negotiate the ethical difficulties surrounding the use of AI in healthcare. Examining the possible advantages, difficulties, and prospects of AI-enhanced health counseling, this literature review explores the state of the field today. The development of a taxonomy of AI dangers in the healthcare domain aims to tackle new issues arising from the application of AI in the medical and healthcare industries. A major benefit of using AI-enhanced health counseling is that it may offer individualized therapies. This individualized approach reflects a holistic view of health by taking into account aspects of mental, emotional, and social well-being in addition to physical health concerns. AI-enhanced health counseling may be able to help with the accessibility and cost issues that come with traditional counseling services. Regardless of location, virtual counselors provide handy support via computers, tablets, and smartphones. When compared to conventional in-person counseling sessions, these AI-based therapies more affordable and scalable.